Arqueología y sociedad. Una percepción acerca de los discursos sobre el pasado prehispánico y su divulgación pública - Segura Llanos, Rafael (2006)
Besides protecting the archaeological legacy, Peruvian archaeologists have emphasized a strong positive discourse on Andean history. Through social channels such as media, museums, and schools, this discourse has apparently been strengthened by a number of recent archaeological finds; sorne of which display a special singularity or material wealth. While the recent collective interest of such a luxurious and exotic past has provided new opportunities for professional development, as well as invigorating the national pride, we should ask ourselves to what extent these views rely thoroughly on scientific practices and how much it distorts the actual variety of the Peruvian historical legacy.